THE TRANS-SAHARAN GAS PIPELINE: AN OVERVIEW OF THE THREATS TO ITS SUCCESS AND THE MEANS TO PREVENT ITS FAILURE (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The purpose of this Article is to highlight and analyze the factors that are likely to affect an investor's decision regarding the TSGP project.  Part I focuses on arguments that support the necessity and viability of this cross border pipeline.  Part II examines factors weighing against the project. Finally, Part III focuses on the main aspects that should be addressed in structuring the TSGP contracts and agreements so as to maximize its potential for success.